1972
DOI: 10.1177/002188637200800503
|View full text |Cite
|
Sign up to set email alerts
|

"Touch Me, Like Me": Testing an Encounter Group Assumption

Abstract: An experiment to test an encounter group assumption that touching increases interpersonal attraction was conducted. Twenty-one college women were randomly assigned to a touch or no-touch condition. In the touch condition the subject was paired with an experimental accomplice who joined her in three bogus ESP experiments, the last of which involved mutual touching for 11o seconds. The no-touch condition was identical, save touching. Subjects then evaluated the experimental accomplice on four dimensions. A compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1974
1974
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…Research has already shown that observers consider touch to be more expected from attractive, higher-status, and equal-status communicators than from unattractive and lower-status ones (Burgoon & Walther, 1990). Because touch is open to multiple interpretations (Heslin & Alper, 1983)-ranging from warmth, affection, involvement, and intimacy (Beier & Stemberg, 1977;Boderman, Freed, & Kinnucan, 1972;Breed & Ricci, 1973;Fisher, Rytting, & Heslin, 1976) to dominance, status, power, and agppssion (Henley 1977;Henley & Harmon, 1985;Major & Heslin, 1982;Summerhayes & Suchner, 1978)-it appears plausible that communicator valence could also alter interpretations. Predictions for touch evaluations should parallel those for interpretations and are bolstered by the finding that some touches are seen as more desirable when committed by an attractive partner than by an unattractive partner (Burgoon & Walther, 1990).…”
Section: Tion?mentioning
confidence: 99%
“…Research has already shown that observers consider touch to be more expected from attractive, higher-status, and equal-status communicators than from unattractive and lower-status ones (Burgoon & Walther, 1990). Because touch is open to multiple interpretations (Heslin & Alper, 1983)-ranging from warmth, affection, involvement, and intimacy (Beier & Stemberg, 1977;Boderman, Freed, & Kinnucan, 1972;Breed & Ricci, 1973;Fisher, Rytting, & Heslin, 1976) to dominance, status, power, and agppssion (Henley 1977;Henley & Harmon, 1985;Major & Heslin, 1982;Summerhayes & Suchner, 1978)-it appears plausible that communicator valence could also alter interpretations. Predictions for touch evaluations should parallel those for interpretations and are bolstered by the finding that some touches are seen as more desirable when committed by an attractive partner than by an unattractive partner (Burgoon & Walther, 1990).…”
Section: Tion?mentioning
confidence: 99%
“…(Despite our own intense sniffing of the literature, we found no work on smelling--or tasting either.) In two different studies--one conducted in the labora tory (35) and the other at a library checkout I�ounter (99)-female respondents were found to like a previously unknown confederate better after a brief touch on the hand than after no touch. Males, who participated in equal numbers in the second study, showed no consistent positive effect.…”
Section: Nonverbal Interactionmentioning
confidence: 99%
“…In addition to role playing, exercises involving physical contact were employed. Such contact has been shown to increase interpersonal attraction (Boderman et al, 1972). Another explanation is that more positive reinforcement may have been provided in role-rehearsal than discussion groups.…”
Section: Discussionmentioning
confidence: 99%